GAMBARAN PERILAKU PRO LINGKUNGAN PADA MASYARAKAT DI KECAMATAN KANDANGAN - Fitria, Aisha; Corinna Marsha, Gladis; Fitriah, Aziza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pro-environmental behaviour refers to actions taken by individuals or groups to reduce negative impacts on the environment and conserve natural resources, which can be seen from indicators of pro-environmental behaviour, such as recycling, environmentally responsible consumption, energy conservation, and transportation behaviour. This study focuses on further exploring the description of pro-environmental behaviour among the community in Kandangan Subdistrict. This study uses quantitative descriptive statistical analysis techniques. The population is 51,847 people, and a sample of 0.5% was taken with a 95% confidence level, resulting in a sample of 259 respondents. This sample size is also in accordance with the general sampling guidelines by Roscoe (1975) in Azwar (2017), which states that statistically, a sample size of more than 30 and less than 500 people is sufficiently representative. The sampling technique used in this study was purposive sampling. Data collection was conducted using the Pro-Environmental Behaviour instrument, with the research focusing on four behavioural indicators that describe pro-environmental behaviour in the Kandangan sub-district community.